Ductal Mucus Obstruction and Reduced Fluid Secretion Are Early Defects in Chronic Pancreatitis - Balázs, Anita; Balla, Zsolt; Kui, Balázs; Maléth, József; Rakonczay, Zoltán; Duerr, Julia; Zhou-Suckow, Zhe; Schatterny, Jolanthe; Sendler, Matthias; Mayerle, Julia; Kühn, Jens-P.; Tiszlavicz, László; et al. (Frontiers in Physiology, 2018)
Objective: Defective mucus production in the pancreas may be an important factor in the initiation and progression of chronic pancreatitis (CP), therefore we aimed to (i) investigate the qualitative and quantitative changes of mucus both in human CP and in an experimental pancreatitis model and (ii) to correlate the mucus phenotype with epithelial ion transport function. Design: Utilizing human tissue samples and a murine model of cerulein induced CP we measured pancreatic ductal mucus content by morphometric analysis and the relative expression of different mucins in health and disease. Pancreatic fluid secretion in CP model was measured in vivo by magnetic resonance cholangiopancreatography (MRCP) and in vitro on cultured pancreatic ducts. Time-changes of ductal secretory function was correlated to those of the mucin production. Results: We demonstrate increased mucus content in the small pancreatic ducts in CP. Secretory mucins MUC6 and MUC5B were upregulated in human, Muc6 in mouse CP. In vivo and in vitro fluid secretion was decreased in cerulein-induced CP. Analysis of time-course changes showed that impaired ductal ion transport is paralleled by increased Muc6 expression. Conclusion: Mucus accumulation in the small ducts is a combined effect of mucus hypersecretion and epithelial fluid secretion defect, which may lead to ductal obstruction. These results suggest that imbalance of mucus homeostasis may have an important role in the early-phase development of CP, which may have novel diagnostic and therapeutic implications.